IMPLEMENTASI ENVIRONMENTAL MANAGEMENT ACCOUNTING DAN NILAI PERUSAHAAN: KINERJA OPERASIONAL PERUSAHAAN SEBAGAI PEMEDIASI - Ester Putri Gita Pratiwi; Dyna Rachmawati (AJAR, 2021)
The aim of this study is to test the implementation of environmental management accounting (EMA) on firm value indirectly through operational performance. EMA consists of Monetary Environmental Management Accounting (MEMA) and Physical Environmental Management Accounting (PEMA). This study uses 329 and 325 firm respectively for MEMA and PEMA. Research samples are manufacturing companies listed in Indonesian Stock Exchange during the period of 2017-2019. The results show that EMA, MEMA, and PEMA have no statistically effect on either to operational performance and firms’ value. It indicates that operational performance has no mediating role in the relationship between EMA and firm’s value. This study uses robustness test by replacing MEMA, PEMA with Environmental Quality Cost (EQC) approach as the measurement of EMA. EQC consists of prevention, detection, internal failure and external failure. The robustness test shows that EQC has positive impact on firms’ value indirectly through operational performance. It means that operational performance has mediating role in the relationship between EQC and firm’s value. This study contributes academically that EQC approach is the best measurement for EMA in manufacturing companies. Therefore, we suggest for the next study can adopt the EQC approach as the measurement of EMA.